A cervical ligamentum flavum cyst in an 82-year-old woman presenting with spinal cord compression: a case report and review of the literature - Brotis Alexandros G; Kapsalaki Eftychia Z; Papadopoulos Evangelos K; Fountas Kostas N (Journal of Medical Case Reports, 2012)
Abstract Introduction We report on a very rare case of a cervical ligamentum flavum cyst, which presented with progressive myelopathy and radiculopathy. The cyst was radically extirpated and our patient showed significant recovery. A review of the relevant literature yielded seven cases. Case presentation An 82-year-old Greek woman presented with progressive bilateral weakness of her upper extremities and causalgia, cervical pain, episodes of upper extremity numbness and significant walking difficulties. Her neurological examination showed diffusely decreased motor strength in both her upper and lower extremities. Magnetic resonance imaging of her cervical spine demonstrated a large, well-demarcated cystic lesion on the dorsal aspect of her spinal cord at the C3 to C4 level, significantly compressing the spinal cord at this level, in close proximity to the yellow ligament and the C3 left lamina. The largest diameter of this lesion was 1.4 cm, and there was no lesion enhancement after the intravenous administration of a paramagnetic contrast. The lesion was surgically removed after a bilateral C3 laminectomy. The thick cystic wall was yellow and fibro-elastic in consistency, while its content was gelatinous and yellow-brownish. A postoperative cervical-spine magnetic resonance image was obtained before her discharge, demonstrating decompression of her spinal cord and dural expansion. Her six-month follow-up evaluation revealed complete resolution of her walking difficulties, improvement in the muscle strength of her arms (4+/5 in all the affected muscle groups), no causalgia and a significant decrease in her preoperative upper extremity numbness. Conclusion Cervical ligamentum flavum cysts are rare benign lesions, which should be included in the list of differential diagnosis of spinal cystic lesions. They can be differentiated from other intracanalicular lesions by their hypointense appearance on T1-weighted and hyperintense appearance on T2-weighted magnetic resonance images, with contrast enhancement of the cystic wall. Surgical extirpation of the cyst is required for symptom alleviation and decompression of the spinal cord. The outcome of these cysts is excellent with no risk of recurrence.